Fully Additive Electrohydrodynamic Inkjet‐Printed TiO2 Mid‐Infrared Meta‐Optics. Issue 19 (12th June 2022) - Brunner, Holly J. C.; Whitehead, James; Gibson, Ricky; Hendrickson, Joshua R.; Majumdar, Arka; MacKenzie, J. Devin
Abstract: Additive manufacturing at the micron and sub‐micron scale is a rapidly expanding field with electrohydrodynamic inkjet (EHDIJ) printing proving to be a critical fabrication technique that will enable continued advancement. Increasing the range of materials that can be used with EHDIJ printing to create micron and sub‐micron scale features is critical for increasing the variety of devices that can be fabricated with this method. Ceramic, semiconducting, and hybrid organic–inorganic materials are essential for meta‐optics and micro‐electromechanical systems devices, yet these materials are vastly underexplored for applications in EHDIJ printing. A novel printing solution is presented containing a titania alkoxide precursor that is compatible with EHDIJ printing and capable of producing final printed features of 1 µm and below; the highest resolution features ever reported for this family of materials and this method. This solution is used to fabricate the first EHDIJ printed and functioning mid‐infrared meta‐optics lens, capable of focusing 5 µm light. Abstract : A novel titania alkoxide printing solution compatible with electrohydrodynamic inkjet (EHDIJ) printing and capable of producing printed features of 1 µm and below is presented. These are the highest resolution features ever reported for this family of materials and methods. This solution is used to fabricate the first functioning EHDIJ printed mid‐infrared meta‐optics lens, capable of focusing 5 µm light.